A new species of Hedysarum (Fabaceae) from Turkey - Kandemi̇r, Ali̇; Sevi̇ndi̇k, Emre; Yildiz, Faruk; Türkoğlu, Hali̇l İbrahi̇m; Yildiz, Bayram (Phytotaxa, 2023)
Hedysarum yilmazunalii Kandemir, F. Yıldız & H.İ. Turkoğlu is described as a new species from Turkey (Eastern Anatolia). The distribution range of the species is restricted to Kemah and Kemaliye districts in Erzincan province on serpentine soils. Hedysarum yilmazunalii is close to Hedysarum candidissimum Freyn in terms of morphological and molecular data. It is also morphologically close to Hedysarum malatyanum Govaerts. In this study, the morphological comparison of the new species with related species is presented. Molecular studies are also done using nrDNA ITS and cpDNA trnL-F regions. ITS data gives better results in phylogenetic analysis. In addition to the morphological data, the results of DNA analysis of the new species are also discussed.